THE ROLE OF DIFFERENTIATED INSTRUCTION IN FOUNDATIONAL HEALTH SCIENCE EDUCATION: ENHANCING BIOLOGY LEARNING OUTCOMES IN PREUNIVERSITY CURRICULA. - Minh, Long Le Thai; Minh, Khai Truong (Scientific Culture, 2026)
Effective pedagogy in foundational sciences is critical for robust student preparation and subsequent success in specialized health science and medical education programs. Differentiated instruction (DI) is an essential educational approach that adapts teaching strategies, content, and activities to accommodate students’ diverse learning styles, which is vital for mastering complex biological principles that underpin future clinical and medical understanding. This research investigates the impact of utilizing Differentiated Instruction tailored to student learning styles on achievement and engagement within the high school biology curriculum, framed as a key course in the pre-health science educational pipeline. Data were collected from 457 students through structured assessments, learning style inventories, and classroom performance records. The instructional intervention applied tailored teaching methods, including visual diagrams, hands-on experiments, group discussions, and multimedia presentations, aligned with the identified learning styles. Learning outcomes were analyzed using pretest-post test comparisons, and statistical evaluation was performed using IBM SPSS software, including paired t-tests, multivariate ANOVA, Chi-Square test for independence, Kruskal-Wallis Test, and Multiple Regression Analyses (MRA) to determine the significance and strength of the instructional effects. The results showed that differentiated training produced considerable benefits. Experimental group scores increased significantly (Visual: 53.2 → 72.1; Auditory: 51.5 → 66.8; Kinesthetic: 52.1 → 70.2, all p<0.001), but the control group’s score increases were minor (≈2−4 points). MANOVA showed significant effects (Learning Style: Λ=0.78, F=12.34, p<0.001). Regression showed that learning style (β=6.45, p<0.001) and teaching type (β=5.12, p<0.001) were the most significant predictors, followed by prior knowledge (β=4.38) and class participation (β=3.25). The findings strongly support the implementation of DI in health science foundational courses to ensure equitable and effective student preparation. These results offer a valuable pedagogical model for medical and health science educators seeking to enhance comprehension of prerequisite scientific concepts and improve educational quality.